Evaluating ecological and socio-economic system dimensions to improve fisheries management in the Bohai Sea, China - Jie Yin; Jia Wo; Yunzhou Li; Ming Sun; Jacob G. Eurich; Kristin M. Kleisner; Shems B. Jud; Yi Tang; Shu Su; Yaping Ao; Yong Chen (Reviews in Fish Biology and Fisheries, 2026)

Corrigendum to “Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development” [Theriogenology 2026; 118017] - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

Chemical constituents from the aerial parts of Rauvolfia yunnanensis Tsiang and their chemotaxonomic significance - Wanqi Yang; Xiaoyan Cui; Renfeng Ye; Min Jiang; Shijing Tang; Wenjing Dong; Guiguang Cheng; Yaping Liu (Biochemical Systematics and Ecology, 2026)

Deep learning-enabled real-time acoustofluidic sorting for selective microalgae recovery under wastewater-relevant heterogeneous conditions - Zihan Li; Xian Jiang; Wenzhe Gong; Aoyang Tang; Yan Ma; Xia Du; Yaping Xie; Tielin Shi; Zhiyong Liu; Guanglan Liao; Lei Nie (Bioresource Technology, 2026)

Promoting the lattice oxygen mechanism via electronic modulation: Cobalt doping and heterointerface effects in RuO2@CuO for enhanced acidic oxygen evolution catalysis - Yuhe Zhang; Yuhui Sun; Yuchen Yang; Yaping Tang; Wei Jiang; Xianyu Chu; Chunbo Liu; jihui Lang; Yuanyuan Wu; Feifan Guo (Chemical Engineering Journal, 2026)

Characterisation of ginsenosides composition in processed American ginseng products using UPLC-MS coupled with chemometric analysis - Chang Wang; Xiaolei Tang; Haiyu Chen; Yaping Wang; Xitong Yuan; Daqing Zhao; Baotai Huang; Li Liu; Bin Qi (Natural Product Research, 2026)

Corrigendum to “Busulfan plus cyclophosphamide induced spermatogenic dysfunction and recovery: A dynamic change perspective” [Toxicol. Lett. 417(2026) 111833] - Tianyu Li; Zhichen Tang; Yaping Song; Min Su; Xiao Liu; Fuping Li; Xing Wei; Xiaolei Luo; Bin Zhou; Yanyun Wang; Lin Zhang (Toxicology Letters, 2026)

Busulfan plus cyclophosphamide induced spermatogenic dysfunction and recovery: A dynamic change perspective - Tianyu Li; Zhichen Tang; Yaping Song; Min Su; Xiao Liu; Fuping Li; Xing Wei; Xiaolei Luo; Bin Zhou; Yanyun Wang; Lin Zhang (Toxicology Letters, 2026)

Breaking the trade-off: Trichoderma effector Tahfb1 dual-targets growth and defense pathways via Hsp70L - Yaping Yin; Yuhang Fu; He Wu; Liping Feng; Lijuan He; Runmao Lin; Rui Wang; Zhengbin Tang; Baoping Zhu; Jumei Hou; Jing Zhao; Tong Liu (Pesticide Biochemistry and Physiology, 2026)

Based on sensory evaluation, E-nose, and GC-IMS analysis of volatile component differences in various kinds of sheep fats - Yaping Wang; Xiaolei Tang; Xitong Yuan; Hanying Xu; Yuxi Liu; Yaling Yang; Zhihui Lin; Siming Wang; Bin Qi; Li Liu (Natural Product Research, 2026)

An mRNA microsphere vaccine inhibiting overactivation of DNA sensing mechanisms - Fangke Zhang; Jiancheng Zheng; Fei Wang; Yaping Zhuang; Yunkai Tang; Juan Wang; Yawei Du; Wei-Li Zhao; Min Lu; Weiguo Hu; Wenguo Cui (Science Bulletin, 2026)

Quantitative and qualitative comparison of grain-size parameters in different types of sediments using graphic and moment methods - Yuehua Qi; Mingliang Li; Gaocong Li; Jieping Tang; Lintao Zhao; Yaping Wang; Mingming Yuan (Acta Oceanologica Sinica, 2026)

Tiered biomimetic polydimethylsiloxane coated polyurethane sponge for sustainable seawater nanoplastic removal - Yuxin Zheng; Yuanyuan Luo; Shengjia Ma; Shuai Tang; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2025)

Corrigendum to “The role of ribosomal protein StRPS5 in mediating resistance of Solanum tuberosum plants to Phytophthora infestans” [Plant Sci. 357 (2025), 112539] - Jing Liu; Yaping Hu; Xiaoqing Lu; Jifen Xu; Hongyang Wang; Wei Tang; Canhui Li (Plant Science, 2025)

Corrigendum to “The role of ribosomal protein StRPS5 in mediating resistance of Solanum tuberosum plants to Phytophthora infestans“ [Plant Sci. 357 (2025) 112539] - Jing Liu; Yaping Hu; Xiaoqing Lu; Jifen Xu; Hongyang Wang; Wei Tang; Canhui Li (Plant Science, 2025)

The role of ribosomal protein StRPS5 in mediating resistance of Solanum tuberosum plants to Phytophthora infestans - Jing Liu; Yaping Hu; Xiaoqing Lu; Jifen Xu; Hongyang Wang; Wei Tang; Canhui Li (Plant Science, 2025)

Structural remodeling of UiO-66(Ce) into oxygen vacancy defect-rich CeO2: Enhancing selective adsorption of As(III) - Tao Zhang; Xu Tang; Jing Xing; Huan Xu; Ruyu Yan; Yaping Zhao (Journal of Hazardous Materials, 2025)

Polyanionic hydrogel electrolytes applied to interface-stabilized zinc ion hybrid capacitors - Pengyun Xie; Xin Wang; Yaping Jiang; Ying Tang; Kaifa Dong; Hui Peng; Guofu Ma; Ziqiang Lei (Chemical Engineering Journal, 2025)

The alleviating effects and mechanisms of Lactiplantibacillus plantarum MC14 on hyperuricemia in mice - Jie Xiong; Jia-Juan Wu; Dong-mei Liu; Muhammad Yousaf; Liu-Jun Liu; Suping Zeng; Qinqin Li; Jun Tang; Yaping Wu (Food Bioscience, 2024)

Sinensetin from citrus peel alleviates DSS-induced inflammation by regulating gut microbiota and serum metabolism in mice - Zuomin Hu; Zhongxing Chu; Xuke Ling; Yuchi Wu; Dandan Qin; Feiyan Yang; Xudong Yu; Yaping Zhou; Yiping Tang; Feijun Luo (Food Bioscience, 2024)

ZnO nanoparticles induce melanoma-like lesions via recruiting dermal dendritic cells in barrier-damaged skin in mice - Menghan You; Yingying Huang; Yeda Chen; Dan Li; Yaping Tang; Yi kuan Du; Hong Yang; Anfa Liang; Guodong Hu; Yinghua Chen (Food and Chemical Toxicology, 2024)

Assessment of uric acid-lowering activity, safety and stress tolerance of Lactiplantibacillus plantarum MC14 based on whole gene sequencing and phenotyping experiments - Jie Xiong; Lingxing Feng; Muhammad Yousaf; Suping Zeng; Jun Tang; Yaping Wu; Qinqin Li; Dong-mei Liu (Food Bioscience, 2024)

Upcycling polystyrene microplastics to Fe/Mo-doped sponge-carbon: Mo5+ enhanced electron transfer for boosting Fenton-like performance - Shengjia Ma; Shuai Tang; Yaping Zhao (Chemical Engineering Journal, 2024)

Carrier effects of face mask-derived microplastics on metal ions: Enhanced adsorption by photoaging combined with biofilms, exemplified with Pb(Ⅱ) - Shuai Tang; Shengjia Ma; Lujian Lin; Yimei Ding; Xiaoting Zhang; Xiaowei Wu; Qun Zhang; Md. Nahid Pervez; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2024)

Fabric structure and polymer composition as key contributors to micro(nano)plastic contamination in face masks - Shuai Tang; Qun Zhang; Haowen Xu; Mengyuan Zhu; Md. Nahid Pervez; Bing Wu; Yaping Zhao (Journal of Hazardous Materials, 2024)

Network pharmacology combined with molecular docking and molecular dynamic simulation to reveal the potential mechanism of lentinan ameliorating hyperlipidemia - Zhongxing Chu; Linna Zeng; Feiyan Yang; Zuomin Hu; Yi Luo; Yaping Zhou; Yiping Tang; Feijun Luo (Food Bioscience, 2024)

Increased overyielding probability and yield stability from a 5-year cotton-based intercropping - Yurui Tang; Yurong Qiu; Xin Li; Haoyue Qin; Jian Wang; Shijie Zhang; Yingchun Han; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Shiwu Xiong; et al. (European Journal of Agronomy, 2024)

Efficient biostimulation of microbial dechlorination of polychlorinated biphenyls by acetate and lactate under nitrate reducing conditions: Insights into dechlorination pathways and functional genes - Yan Xu; Ying Wang; An Zheng; Yaping Yuan; Lei Xu; Yanqiang Tang; Qingdong Qin (Journal of Hazardous Materials, 2024)

Effects of transition-metal ions on the reduction of N-nitrosodimethylamine in water by zinc - Ying Han; Xiaoping Zheng; Beibei Jiang; Yuling Tang; Hongyuan Liu; Kemin Zhang; Yaping Guo; Jun Li (Journal of Environmental Chemical Engineering, 2024)

The miR-34b/MEK/ERK pathway is regulated by NR5A1 and promotes differentiation in primary bovine Sertoli cells - Qibing Tao; Linlin Zhang; Yun Zhang; Mingming Liu; Jie Wang; Qian Zhang; Jiancheng Wu; Aihua Wang; Yaping Jin; Keqiong Tang (Theriogenology, 2024)

A Review of Electrochemical Treatment Processes of Leachate Membrane Concentrate - Peixin Tang; Xu Ren; Zhicheng Pan; Meng Shen; Danni Peng; Yucheng Liu; Yaping Zhong; Yumei Peng; Xin Peng (Water, Air, & Soil Pollution, 2024)

MiR-7 deficiency promotes Th1 polarization of CD4+T cells and enhances the antitumor effect in adoptive cell therapy for lung cancer - Xian Chang; Juanjuan Zhao; Ya Zhou; Mengmeng Guo; Yaping Yan; Ya Wang; Xu Zhao; Jing Yang; Chao Chen; Lin Tang; Ming Qin; Lin Xu (Immunologic Research, 2024)

Enhanced peroxymonosulfate activation via heteroatomic doping defects of pyridinic and pyrrolic N in 2D N‑doped carbon nanosheets for BPA degradation - Guojuan Qu; Peng Jia; Shuai Tang; Md. Nahid Pervez; Yixiong Pang; Bin Li; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2024)

Valorization of meat and bone residue by ultrasound and high voltage electrostatic field assisted two-stage enzymatic hydrolysis: Nutritional characteristics and flavor analysis - Tiantian Tang; Min Zhang; Yaping Liu (Food Bioscience, 2023)

Tea polyphenols coated sodium alginate-gelatin 3D edible scaffold for cultured meat - Xiaohong Chen; Linzi Li; Lin Chen; Wei Shao; Yan Chen; Xiaojing Fan; Yaping Liu; Changbo Tang; Shijie Ding; Xinglian Xu; Guanghong Zhou; Xianchao Feng (Food Research International, 2023)

Directly linking plant N, P and K nutrition to biomass production in cotton-based intercropping systems - Yurong Qiu; Xin Li; Yurui Tang; Shiwu Xiong; Yingchun Han; Zhanbiao Wang; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Wenli Du; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

Synergistic activation of peroxymonosulfate by intrinsic defect and graphitic N of N, P co-doped carbon microspheres for BPA degradation - Guojuan Qu; Peng Jia; Tao Zhang; Shuai Tang; Md. Nahid Pervez; Yixiong Pang; Bin Li; Chengjin Cao; Yaping Zhao (Chemical Engineering Journal, 2023)

NR1 Splicing Variant NR1a in Cerebellar Granule Neurons Constitutes a Better Motor Learning in the Mouse - Ting Tan; Linyan Jiang; Zhengxiao He; Xuejiao Ding; Xiaoli Xiong; Mingxi Tang; Yuan Chen; Yaping Tang (The Cerebellum, 2023)
As an excitatory neuron in the cerebellum, the granule cells play a crucial role in motor learning. The assembly of NMDAR in these neurons varies in developmental stages, while the significance of this variety is still not clear. In this study, we found that motor training could specially upregulate the expression level of NR1a, a splicing form of NR1 subunit. Interestingly, overexpression of this splicing variant in a cerebellar granule cell-specific manner dramatically elevated the NMDAR binding activity. Furthermore, the NR1a transgenic mice did not only show an enhanced motor learning, but also exhibit a higher efficacy for motor training in motor learning. Our results suggested that as a “junior” receptor, NR1a facilitates NMDAR activity as well as motor skill learning.

Catalytic activity and anti-passivation of single iron atoms and atomic clusters co-stabilized on carbonized waste polystyrene plastic - Shengjia Ma; Shuai Tang; Tao Zhang; Wei Jin; Hui Zhu; Yaping Zhao; Dionysios D. Dionysiou (Chemical Engineering Journal, 2023)

Proteomic analysis of uterine lavage fluid of dairy cows at different time after delivery by mass spectrometry - Xingcan Jiang; Ziyuan Li; Xiyu Chang; Cong Huang; Rendong Qiu; Aihua Wang; Pengfei Lin; Keqiong Tang; Huatao Chen; Dong Zhou; Yaping Jin (Theriogenology, 2023)

Sodium acetate trihydrate/melamine foam composite PCM encapsulated by CuS/rGO modified epoxy resin and endowed with light-to-heat conversion properties - Henghua Zhang; Qianbin Dong; Yaping Tang; Jialing Wu; Wenjian Bi; Yue Gao; Jiabang Wang; Hui Yang (Chemical Engineering Journal, 2023)

Photo-aged non-biodegradable and biodegradable mulching film microplastics alter the interfacial behaviors between agricultural soil and inorganic arsenic - Shuai Tang; Peipei Sun; Guojuan Qu; Yue Tian; Junlai Liu; Md. Nahid Pervez; Xiuyan Li; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2023)

Effects of ultrasound combined technology on quality and volatile compound properties of chili sauce - Tiantian Tang; Min Zhang; Chung Lim Law; Yaping Liu (Food Bioscience, 2023)

Identification of nsLTP family in Chinese white pear (Pyrus bretschneideri) reveals its potential roles in russet skin formation - Jiawei Li; Qi Wang; Yajing Wang; Xinyi Wu; Yaping Liu; Minchen Wan; Lindu Wang; Xiexuan Wang; Cheng Zhang; Xueqian Wang; Xiaomei Tang; Wei Heng (Planta, 2023)

Sorption of bisphenol A onto microplastics and associated environmental risks in comparison to engineered carbonous materials and natural media - Shuai Tang; Shengjia Ma; Tao Zhang; Xuemin Liu; Md. Nahid Pervez; Chengjin Cao; Yaping Zhao (Gondwana Research, 2023)

The interfacial behaviors of different arsenic species on polyethylene mulching film microplastics: Roles of the plastic additives - Shuai Tang; Peipei Sun; Shengjia Ma; Wei Jin; Yaping Zhao (Journal of Hazardous Materials, 2023)

Carbon layer encapsulation strategy for designing multifunctional core-shell nanorod aerogels as high-temperature thermal superinsulators - Fengqi Liu; Chenbo He; Yonggang Jiang; Yaping Yang; Fei Peng; Lanfang Liu; Jing Men; Junzong Feng; Liangjun Li; Guihua Tang; Jian Feng (Chemical Engineering Journal, 2023)

Induced mutation in ELONGATED HYPOCOTYL5 abolishes anthocyanin accumulation in the hypocotyl of pepper - Rong Chen; Can Yang; Hu Gao; Chunmei Shi; Zhiying Zhang; Guangyu Lu; Xinyan Shen; Yaping Tang; Feng Li; Yongen Lu; Bo Ouyang (Theoretical and Applied Genetics, 2022)

A New Dual-peak Fluorescent Probe for Water Content Detection Made From Taxus - Gang Wang; Yaping Li; Haipeng Chen; Shuqin Tang; Yiyang Cheng; Yuhong Yu; Abdul Qayoom Majeedano; Shangrao Pu; Gang Wang (Journal of Fluorescence, 2022)

The inhibitory effects of the antifouling compound Irgarol 1051 on the marine diatom Skeletonema sp. across a broad range of photosynthetically active radiation - Yao Tang; Cheng Chen; Yangjie Sheng; Peijian Ding; Xinyu Wu; John Beardall; Yaping Wu (Environmental Science and Pollution Research, 2021)

A 2-step algorithm combining glutamate dehydrogenase and nucleic acid amplification tests for the detection of Clostridioides difficile in stool specimens - Chengcheng Liu; Chenjie Tang; Yaping Han; Yuqiao Xu; Fang Ni; Ke Jin; Genyan Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Choline–betaine pathway contributes to hyperosmotic stress and subsequent lethal stress resistance in Pseudomonas protegens SN15-2 - Danyan Tang; Xiaobing Wang; Jian Wang; Mengfei Wang; Yaping Wang; Wei Wang (Journal of Biosciences, 2020)

Interactive effects of exogenous melatonin and Rhizophagus intraradices on saline-alkaline stress tolerance in Leymus chinensis - Yurong Yang; Yaping Cao; Zhenxin Li; Anastasiia Zhukova; Songtao Yang; Jinlong Wang; Zhanhui Tang; Yonghong Cao; Yifei Zhang; Deli Wang (Mycorrhiza, 2020)

Immunity induced by recombinant attenuated IHNV (infectious hematopoietic necrosis virus)‐G N438A expresses VP2 gene‐encoded IPNV (infectious pancreatic necrosis virus) against both pathogens in rainbow trout - Yaping Chen; Mengting Guo; Yanxue Wang; Xiaojing Hua; Shuai Gao; Yuting Wang; Dechuan Li; Wen Shi; Lijie Tang; Yijing Li; Min Liu (Journal of Fish Diseases, 2019)
Infectious hematopoietic necrosis virus (IHNV) and infectious pancreatic necrosis virus (IPNV) are important pathogens in rainbow trout farming worldwide. Their co‐infection is also common, which causes great economic loss in juvenile salmon species. Development of a universal virus vaccine providing broadly cross‐protective immunity will be of great importance. In this study, we generated two recombinant (r) virus (rIHNV‐N438A‐ΔNV‐EGFP and rIHNV‐N438A‐ΔNV‐VP2) replacing the NV gene of the backbone of rIHNV at the single point mutation at residue 438 with an efficient green fluorescent protein ( EGFP ) reporter gene and antigenic VP2 gene of IPNV. Meanwhile, we tested their efficacy against the wild‐type (wt) IHNV HLJ‐09 virus and IPNV serotype Sp virus challenge. The relative per cent survival rates of two recombinant viruses against (wt) IHNV HLJ‐09 virus challenge were 84.6% and 81.5%, respectively. Simultaneously, the relative per cent survival rate of rIHNV‐N438A‐ΔNV‐VP2 against IPNV serotype Sp virus challenge was 88.9%. It showed the two recombinant viruses had high protection rates and induced a high level of antibodies against IHNV or IPNV. Taken together, these results suggest the VP2 gene of IPNV can act as candidate gene for vaccine and attenuated multivalent live vaccines and molecular marker vaccines have potential application for viral vaccine.

Comparative genomics for non-O1/O139 Vibrio cholerae isolates recovered from the Yangtze River Estuary versus V. cholerae representative isolates from serogroup O1 - Li Gong; Pan Yu; Huajun Zheng; Wenyi Gu; Wei He; Yadong Tang; Yaping Wang; Yue Dong; Xu Peng; Qunxin She; Lu Xie; Lanming Chen (Molecular Genetics and Genomics, 2019)

Correlation of IL-31 gene polymorphisms with susceptibility and clinical recurrence of bladder cancer - Qin Li; Tielong Tang; Peng Zhang; Chenlu Liu; Yan Pu; Yan Zhang; Huizi Song; Yanyun Wang; Yaping Song; Min Su; Bin Zhou; Lin Zhang (Familial Cancer, 2018)

Dolomitization by penesaline sea water in Early Cambrian Longwangmiao Formation, central Sichuan Basin, China - Xuefei Yang; Hao Tang; Xingzhi Wang; Yaping Wang; Yueming Yang (Journal of Earth Science, 2017)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Molecular and biochemical characterizations of a new low-temperature active mannanase - Rui Zhang; Junpei Zhou; Yajie Gao; Yaping Guan; Junjun Li; Xianghua Tang; Bo Xu; Junmei Ding; Zunxi Huang (Folia Microbiologica, 2015)

High-level expression and characterization of a thermophilic β-mannanase from Aspergillus niger in Pichia pastoris - Shi Yu; Zhezhe Li; Yaping Wang; Wanping Chen; Lin Fu; Wei Tang; Chen Chen; Yunyun Liu; Xue Zhang; Lixin Ma (Biotechnology Letters, 2015)

Expression and functional analysis of a glycoside hydrolase family 45 endoglucanase from Rhizopus stolonifer - Bin Tang; Yingying Zhang; Yaping Yang; Zhewei Song; Xianglin Li (World Journal of Microbiology and Biotechnology, 2014)

Molecular characterization, polymorphism of bovine ZBTB38 gene and association with body measurement traits in native Chinese cattle breeds - Yongfeng Liu; Linsen Zan; Shuanping Zhao; Yaping Xin; Linqiang Li; Wentao Cui; Zhonglin Tang; Kui Li (Molecular Biology Reports, 2010)

The role of MC1R gene in buffalo coat color - YongWang Miao; GuiSheng Wu; Lei Wang; DaLin Li; ShouKun Tang; JianPing Liang; HuaMing Mao; HuaiRong Luo; YaPing Zhang (Science China Life Sciences, 2010)